MANAGEMENT OF UTERINE TORSION IN BUFFALOES - Mudasir, Qazi; Shukla, S P; Nema, S P (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
Ten pluriparous full term pregnant Murrah buffaloes were admitted in Teaching Veterinary Clinical Service Complex, College of Veterinary Science & A.H Mhow with history of restlessness and excessive straining with no progress in parturition from last 12-36 hours. Uterine torsion was confirmed by rectal and vaginal examination. The degree (angle),direction (Right or left) and location of torsion (pre or post cervical) was identified.Sucessful detorsion was achieved by Schaffers method in eight cases and rest two protracted cases needed surgical intervention(cesarean section).The survival rate was 100% in Schaffer`s method, while one among the two buffaloes undergoing cesarean section died after 12 hrs of operation.Of these eight cases solved by Schaffer`s method four live calves were delivered.It was concluded that Schaffer`s method is an effective method to relieve uterine torsion with better survival rates,however in protracted cases surgical intervention is the method of choice.
Keywords: Pluriparous; Murrah; Restlessness; Straining